Correlation of APGAR family with mental health: an observational study in Indonesia - Aziz, Yusuf Abdullah; Susanto, Syarafina Ayu Putri; Romadhon, Yusuf Alam (International Journal of Health Science and Technology, 2023)
Mental health disorders adversely affect their general health and quality of life (Wang et al., 2020). In Indonesia, the prevalence in 2018 was 6.1%, and mental-emotional disorders were 9.8% (Kemenkes RI, 2019). A systematic review reported that in many studies, it is stated that the family has a protective role against mental health disorders or behaviors that affect mental health in general (Wlodarczyk et al., 2017). Studies specifically evaluating the effect of family functioning on mental health in the presence of symptoms of depression, anxiety, and stress are limited. This study used a cross-sectional study design, evaluating the relationship between family functioning and mental health at one time. This study outputs data from Field Lab activities in the Public Health and Family Medicine Block and Life Skills Block in two different batches in 2020 and 2021 at the Faculty of Medicine, Universitas Muhammadiyah Surakarta. A total of 1475 research subjects voluntarily participated in this study. In this study, multivariate analysis of statistically consistent variables highly significant on depression, anxiety, and stress is APGAR Family, with p values of 0.000, 0.000, and 0.001, respectively. The second statistically consistent variable is a significant - highly significant effect on the level of depression, anxiety, and stress with p values of 0.001, 0.015, and 0.001, respectively. A dysfunctional family and unmarriedness are consistent risk factors for depression, anxiety, and stress disorders.